Prenatal polycyclic aromatic hydrocarbon exposure and asthma at age 8–9 years in a multi-site longitudinal study - Allison R. Sherris; Christine T. Loftus; Adam A. Szpiro; Logan C. Dearborn; Marnie F. Hazlehurst; Kecia N. Carroll; Paul E. Moore; Margaret A. Adgent; Emily S. Barrett; Nicole R. Bush; Drew B. Day; Kurunthachalam Kannan; et al. (Environmental Health, 2024)
Abstract Background and aim Studies suggest prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) may influence wheezing or asthma in preschool-aged children. However, the impact of prenatal PAH exposure on asthma and wheeze in middle childhood remain unclear. We investigated these associations in socio-demographically diverse participants from the ECHO PATHWAYS multi-cohort consortium. Methods We included 1,081 birth parent–child dyads across five U.S. cities. Maternal urinary mono-hydroxylated PAH metabolite concentrations (OH-PAH) were measured during mid-pregnancy. Asthma at age 8–9 years and wheezing trajectory across childhood were characterized by caregiver reported asthma diagnosis and asthma/wheeze symptoms. We used logistic and multinomial regression to estimate odds ratios of asthma and childhood wheezing trajectories associated with five individual OH-PAHs, adjusting for urine specific gravity, various maternal and child characteristics, study site, prenatal and postnatal smoke exposure, and birth year and season in single metabolite and mutually adjusted models. We used multiplicative interaction terms to evaluate effect modification by child sex and explored OH-PAH mixture effects through Weighted Quantile Sum regression. Results The prevalence of asthma in the study population was 10%. We found limited evidence of adverse associations between pregnancy OH-PAH concentrations and asthma or wheezing trajectories. We observed adverse associations between 1/9-hydroxyphenanthrene and asthma and persistent wheeze among girls, and evidence of inverse associations with asthma for 1-hydroxynathpthalene, which was stronger among boys, though tests for effect modification by child sex were not statistically significant. Conclusions In a large, multi-site cohort, we did not find strong evidence of an association between prenatal exposure to PAHs and child asthma at age 8–9 years, though some adverse associations were observed among girls.